Pengaruh Literasi Keuangan, Brand Image, dan Digital Marketing Terhadap Minat Generasi Z di Kabupaten Sukoharjo Menjadi Nasabah Bank Syariah Indonesia - Rifai Hakim Bintang Wiyadi; Noer Sasongko (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of financial literacy, brand image, and digital marketing on Generation Z’s interest in becoming customers of Bank Syariah Indonesia in Sukoharjo Regency. A quantitative approach with a descriptive method was used. The research sample consisted of 100 respondents selected using purposive sampling based on specific criteria. Data were collected through a questionnaire using a five-point Likert scale. Data analysis was conducted using multiple linear regression, supported by validity tests, reliability tests, and classical assumption tests. The results show that financial literacy significantly influences Generation Z’s interest in becoming customers of Bank Syariah Indonesia, as better financial management understanding increases interest in Islamic banking services. Conversely, brand image does not significantly influence customer interest, likely due to infrastructure limitations, lack of service trust, and less comprehensive product offerings compared to conventional banks. Meanwhile, digital marketing has a significant effect on Generation Z’s interest due to its effectiveness in disseminating information widely and efficiently.